Atrazine Degradation Through a Heterogeneous Dual-Effect Process Using Fe–Tio2-Allophane Catalysts Under Sunlight - Ureta-Zanartu, M (Elsevier Ltd, 2024)
This study investigated the novel application of Fe–TiO2-allophane catalysts with 6.0 % w/w of iron oxide and two TiO2 proportions (10 % and 30 % w/w) for degrading atrazine (ATZ) using the heterogeneous dual-effect (HDE) process under sunlight. Comparative analyses with Fe-allophane and TiO2-allophane catalysts were conducted in both photocatalysis (PC) and HDE processes. FTIR spectra reveal the unique hydrous feldspathoids structure of allophane, showing evidence of new bond formation between Si–O groups of allophane clays and iron hydroxyl species, as well as Si–O–Ti bonds that intensified with higher TiO2 content. The catalysts exhibited an anatase structure. In Fe–TiO2-allophane catalysts, iron oxide was incorporated through the substitution of Ti4+ by Fe3+ in the anatase crystal lattice and precipitation on the surface of allophane clays, forming small iron oxide particles. Allophane clays reduced the agglomeration and particle size of TiO2, resulting in an enhanced specific surface area and pore volume for all catalysts. Iron oxide incorporation decreased the band gap, broadening the photoresponse to visible light. In the PC process, TiO2-allophane achieves 90 % ATZ degradation, attributed to radical species from the UV component of sunlight. In the HDE process, Fe–TiO2-allophane catalysts exhibit synergistic effects, particularly with 30 % w/w TiO2, achieving 100 % ATZ degradation and 85 % COD removal, with shorter reaction time as TiO2 percentage increased. The HDE process was performed under less acidic conditions, achieving complete ATZ degradation after 6 h without iron leaching. Consequently, Fe–TiO2-allophane catalysts are proposed as a promising alternative for degrading emerging pollutants under environmentally friendly conditions. © 2024